Neutropaenic enterocolitis due to Methotrexate in a patient with Rheumatoid arthritis - a case report - D.P. Jayasena; M.M.P.T. Jayasekera; G.D.S. Govindapala; J.M. Munasinghe; T. Samarawickrama; A. Senanayake; H.A.V. Chaturika; R.A.N.K. Wijensinghe (Sri Lanka College of Internal Medicine, 2022)
Neutropaenic enterocolitis is a rare, life-threatening disease, characterised by fever and abdominal pain in the setting of neutropaenia. Neutropaenic enterocolitis as a complication of medical therapy in patients with rheumatoid arthritis has rarely been reported. Here we describe a patient with rheumatoid arthritis, who developed neutropaenic enterocolitis following a single dose of methotrexate.